Nonsupersymmetric gauge coupling unfication in [SU(6)]4× Z4 and proton stability (1999)
ABSTRACT: We systematically study the three family extension of the Pati-Salam gauge group with an anomaly-free single irreducible representation which contains the known quarks and leptons without mirror fermions. In the context of this model we implement the survival hypothesis, the modified horizontal survival hypothesis, and calculate the tree level masses for the gauge boson and fermion fields. We also use the extended survival hypothesis in order to calculate the mass scales using the renormalization group equation. The interacting Lagrangean with all the known and predicted gauge interactions is explicitly displayed. Finally the stability of the proton in this model is established.